A review of bone grafting techniques for glenoid reconstruction. (April 2022) - Zhang, Jeffrey A; Lam, Patrick H; Beretov, Julia; Murrell, George AC
Background: Traumatic anterior shoulder dislocations can cause bony defects of the anterior glenoid rim and are often associated with recurrent shoulder instability. For large glenoid defects of 20–30% without a mobile bony fragment, glenoid reconstruction with bone grafts is often recommended. This review describes two broad categories of glenoid reconstruction procedures found in literature: coracoid transfers involving the Bristow and Latarjet procedures, and free bone grafting techniques. Methods: An electronic search of MEDLINE and PubMed was conducted to find original articles that described glenoid reconstruction techniques or modifications to existing techniques. Results: Coracoid transfers involve the Bristow and Latarjet procedures. Modifications to these procedures such as arthroscopic execution, method of graft attachment and orientation have been described. Free bone grafts have been obtained from the iliac crest, distal tibia, acromion, distal clavicle and femoral condyle. Conclusion: Both coracoid transfers and free bone grafting procedures are options for reconstructing large bony defects of the anterior glenoid rim and have had similar clinical outcomes. Free bone grafts may offer greater flexibility in graft shaping and choice of graft size depending on the bone stock chosen. Novel developments tend towards minimising invasiveness using arthroscopic approaches and examining alternative non-rigid graft fixation techniques.